Governance and development - Narayan, Jayaprakash (2004)
The economic growth of a country is contingent on the way it governs itself. The way the economic policies are formulated and their implementation is done largely determines whether the country will achieve its targets of growth and development. In essence there is a direct relationship between compliance with rule of law and development indicators. This article examines the state of health care service, infrastructure development, education system and administrative culture in the country. The instances of rampant and high level corruption has deprived a large section of population of the benefits of the various welfare schemes and social security measures. With the advent of economic liberalisation and delicensing the nature of corruption is also undergoing major transformation. Some practical and institutional initiatives to curb corruption have been suggested here. - Reproduced.
Keywords: Good governance